2014
DOI: 10.1038/ismej.2014.245
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomic and metatranscriptomic analyses of microbial communities in acid mine drainage

Abstract: The microbial communities in acid mine drainage have been extensively studied to reveal their roles in acid generation and adaption to this environment. Lacking, however, are integrated community- and organism-wide comparative gene transcriptional analyses that could reveal the response and adaptation mechanisms of these extraordinary microorganisms to different environmental conditions. In this study, comparative metagenomics and metatranscriptomics were performed on microbial assemblages collected from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(180 citation statements)
references
References 64 publications
11
162
0
4
Order By: Relevance
“…While metagenomics, metatranscriptomics, and functional arrays are good approaches for functional analysis [18, 19], these methods are constrained by cost and difficulty [20, 21]. Recently, Langille et al [22] developed the software Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt), which analyzes microbial function by combining phylogenetic analyses and genome database data to predict functional profiles.…”
Section: Introductionmentioning
confidence: 99%
“…While metagenomics, metatranscriptomics, and functional arrays are good approaches for functional analysis [18, 19], these methods are constrained by cost and difficulty [20, 21]. Recently, Langille et al [22] developed the software Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt), which analyzes microbial function by combining phylogenetic analyses and genome database data to predict functional profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, microbial-mediated AMD generation results in a low alpha-diversity of microbial community at the late stage. [27,52,53]. For example, previous metagenomics study of tailings acidification showed that the sulfur oxidation was mainly performed by Thiobacillus at the early stage and by Acidithiobacillus at the late stage [50].…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
“…were found to be predominant at the late oxidation stage, which was usually characterized by low pH (<3.0) and a high concentration of metals [47,49,50], revealing their favorable adaptation of harsh environmental conditions and indispensability in such ecosystems [51]. Metagenomic as well as transcriptomic analyses deciphered significant variations in microbial community function [27,52,53].…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
“…Similar to various acidophiles, Sulfobacillus spp. might generate a reversed membrane potential via the Kdp-type potassium transport system (Table S4), thereby partially deflecting the inward flow of protons (9,65,66). Additionally, genes encoding the Kef-type potassium efflux system and voltage-gated potassium channel proteins were identified in Sulfobacillus genomes.…”
Section: Figmentioning
confidence: 99%